The age-specific normative values of standing whole-body sagittal alignment parameters in healthy adults: based on international multicenter data - Ouchida, Jun; Nakashima, Hiroaki; Kanemura, Tokumi; Okamoto, Masashi; Hatsushikano, Shun; Imagama, Shiro; Le Huec, Jean Charles; Hasegawa, Kazuhiro (European Spine Journal, 2023)
Purpose To investigate the age-specific normative values of whole-body sagittal alignment (WBSA) including global balance parameters in healthy adults and to clarify the correlations among parameters based on the data from three international multicenter. Methods Three hundred and seventeen healthy subjects (range: 20–84 y.o., mean: 43.8 ± 14.7 y.o.) were included and underwent whole-body biplanar X-ray imaging system. Spinopelvic parameters and knee flexion (KF), the center of acoustic meatus (CAM)-hip axis (HA), and C2 dentiform apophyse (OD)-HA, the cranial center (Cr)-HA were evaluated radiologically. Sub-analysis for correlation analysis between age and parameters and among parameters was performed to investigate age-specific change and compensatory mechanisms. Results For age-related change, C2-7 angle ( r = .326 for male/.355 for female), KF ( r = .427/.429), and SVA ( r = .234/.507) increased with age in both male and female group. For global parameters related to the center of the gravity, correlations with age were not significant ( r = .120/.161 for OD-HA, r = .163/.275 for Cr-HA, r = .149/.262 for CAM-HA). Knee flexion (KF) has correlation with global parameters (i.e., SVA, OD-HA, Cr-HA, CAM-HA) and does not have correlations with local spinopelvic alignment. Conclusion While several local alignment changes with age were found, changes in global parameters related to the center of gravity were kept relatively mild by the chain of compensation mechanisms including the lower limbs. We showed the normative values for a comprehensive WBSA in standing posture from large international healthy subjects’ database.